Initialization of the JYFLTRAP system - Pikkarainen, Toni (2013)
The IGISOL facility has been moved into a new location at the acceleration laboratory of the University of Jyväskylä. The superconducting magnet that is part of the JYFLTRAP system has been re-energized. In this thesis a commissioning of the Penning trap apparatus JYFLTRAP is described. This involves a precise alignment of the structure of the trap along field lines of strong solenoid field. The alignment was completed successfully with a special alignment device. In addition, some improvements were done for the Penning traps and transfer line from RFQ cooler, and a buncher to the injection of Penning traps was built during this project.